PREPARASI BIODIESEL DARI MINYAK JELANTAH KELAPA SAWIT - Suirta, I W. (Jurnal Kimia (Journal of Chemistry); Vol. 3, No. 1 Januari 2009)
Synthesis of biodiesel from used cooking oil was carried out in two step reactions i.e esterification and transesterification. The biodiesel obtained was analysed using gas chromatography and mass spectrometer (GC-MS). The quality was determined by comparing its physico chemical properties and compared to the Jerman Standard DIN V 51606. The result of GC-MS showed 6 peaks coresponding to six methyl ester(biodiesel): methyl myristate, methyl palmitate, methyl linoleate, methyl oleate, methyl stearat and methyl arachydate. The biodiesel obtained has a density of (0,8976±0,0003 g/mL), viscosity of (4,53±0,0872 mm/s), acid value of (0,4238±0,0397 mg KOH/g, and iod number of (9,3354±0,0288 g iod/100 g sample). There properties were in a good agreement with the standard Jerman DIN 51606.
Keywords: biodiesel, used cooking oil, Germany standard DIN 51606